Terrestrial ecosystems are in transition - Wang, Huan; Yan, Yuchao; Li, Delong; Li, Xiaojun; Liu, Xiangzhuo; Fan, Lei; Wang, Mengjia; Yao, Ying; Cai, Yiling; Yan, Shijie; Xing, Zanpin; Zheng, Yi; et al. (Frontiers in Remote Sensing, 2025)
Global climate change and accelerating human disturbance may trigger biosphere tipping points across a range of scales and push the terrestrial ecosystem undergoing irreversible critical transitions toward alternative ecosystems. The resilience of these systems—their capacity to resist and recover from perturbations and maintain structure and function—is being eroded by multiple drivers, including land-use change, altered disturbance regimes, and biogeochemical imbalances. These drivers interact in nonlinear ways, generating cascading effects across scales and amplifying the risk of state shifts. Increasing evidence based on remote sensing time series shows that many forests are losing resilience, suggesting an early warning signal for approaching tipping points. Once tipping points are crossed, recovery is highly uncertain or even impossible on human timescales, with profound implications for biodiversity, ecosystem services, and the global carbon cycle. Understanding the mechanisms of resilience loss and identifying early-warning signals of approaching thresholds are therefore central to predicting future ecosystem stability. Due to its ability to monitor key parameters related to vegetation dynamics, remote sensing has emerged as a key tool for monitoring vegetation resilience. This can be done over large areas and with high spatial (about 10 m) and temporal (week-month) resolutions. This review synthesizes current advances on the drivers, evidence, tipping dynamics of terrestrial ecosystems in transition, and advantages of remote sensing in resilience study. We further highlight urgent action to anticipate and manage critical risks, and mitigate climate change in the Anthropocene.